Shell model study of neutron rich 18-28O isotopes using effective interactions - Hamoudi, Adel K.; Bahr, Hussam A. (Iraqi Journal of Science, 2022)
We employ a simple effective nucleon-nucleon interaction for sd-shell model calculations derived from the Reid soft-core potential folded with two-body correlation functions which take account of the strong short-range repulsion and large tensor component in the Reid force. Shell model calculations for ground and low lying energy states of neutron rich oxygen isotopes 18-28O are performed using OXBASH code. Generally, this interaction predicts correct ordering of levels, yields reasonable energies for ground states of considered isotopes and predicts very well the newly observed excitation energy ofin 26O. Besides, it produces reasonable energy spectra for 23-27O and compressed energy spectra for 18-22O isotopes. This is mainly due entirely to defects in thediagonal matrix elements of employed interaction. To improve the present calculations, we modify the interaction through replacing the 14 diagonal matrix elements ofwith those of the USD interaction. Mostly, our modified interaction predicts well the ordering of levels, the ground state energies and low lying energy spectra for all selected oxygen isotopes. The modified interaction confirms the location of the neutron drip line atand also identifies the presence of the shell gap atandwhich proves the doubly magic behavior of 22O and 24O. The spins in 24O of several excitation energies around 7.5 MeV are predicted by our interactions. The calculated results obtained with the modified interaction are very close to those obtained with the empirical interactions of USDB and WPN.